Urinary excretion of 3-phenoxybenzoic acid in middle-aged and elderly general population of Japan - Ueyama, Jun; Kimata, Akiko; Kamijima, Michihiro; Hamajima, Nobuyuki; Ito, Yoshinori; Suzuki, Koji; Inoue, Takashi; Yamamoto, Kanami; Takagi, Kenji; Saito, Isao; Miyamoto, Ken-ichi; Hasegawa, Takaaki; et al. (Environmental research, 2009)
Limited data are available on the background levels of exposure to synthetic pyrethroid (PYR) in Japan, despite their frequent application for agriculture and indoor extermination and possible effects of chronic and/or low-dose PYR exposure on human health. This study was conducted to describe the level and distribution of one of the major PYR metabolites, 3-phenoxybenzoic acid (3-PBA), in urine samples collected from a general population in Japan. The subjects were 535 individuals (184 men and 351 women; 61.5±9.8 years of age, mean±S.D.) residing in a town in Hokkaido, a dairy and agricultural area. Urinary 3-PBA was found detectable in 98% of samples above the limit of detection of 0.02 μg/l. The geometric mean values of urinary 3-PBA in occupationally exposed farmers ( n=87) and the remaining general group without occupational exposure ( n=448) were 0.38 and 0.29 μg/l, respectively, ranging from <LOD to 17.09 μg/l. No significant differences in urinary 3-PBA concentrations were shown between these two groups. Moreover, 3-PBA concentrations were found comparable to those reported in some countries. The present study is, to our knowledge, the first report of a biological monitoring study of urinary 3-PBA, which elucidated the background environmental exposure level of PYR in the Japanese general population without occupational exposure. Further nationwide studies covering different seasons and age distribution are needed to monitor the urinary 3-PBA levels in Japan.